Information and knowledge management: dimensions and approaches - Christian Schlögl (Information Research: An International Electronic Journal, 2005)
Introduction. Though literature on information and knowledge management is vast, there is much confusion concerning the meaning of these terms. Hence, this article should give some orientation and work out the main aspects of information and knowledge management. Method. An author co-citation analysis (ACA), which identified the main dimensions of information management, forms the basis of the study of literature. In it, the main aspects of information management are further refined. Furthermore, it will be investigated if the concept of knowledge management adds anything to information management, and if so what it is. Analysis. Data for ACA were retrieved from Science Citation Index (SCI) and Social Science Citation Index (SSCI). Though the literature review is based on the quantitative results of the bibliometric analysis and has tried to consider the most prominent publications, some degree of subjectivism cannot be excluded. Results. As a result of ACA, a distinction can be made between content and technology-oriented information management approaches. According to the literature review, technology-oriented information management includes data management, IT management and strategic IT management. The main emphasis of these approaches is the effective and efficient use of information technology. In contrast, content-oriented approaches focus on information and its use. They can be distinguished in records management, provision of external information, human-centered information management, and information resources management. The reading of the literature on knowledge management reveals, that this term is either used synonymously for information management or for the management of work practices with the goal to improve the generation of new knowledge and the sharing of existing knowledge. Conclusion. . This article identifies various aspects that are embraced by the terms information management and knowledge management. Thus, it should contribute to more terminological clarity and finally improve communication both in science and in professional practice.